Heat and moisture transfer dynamics in humidity-stratified paddy grain bulk under mechanical ventilation - Qiang Yin; Youjun He; Shuai Liu; Xiaopeng Liu; Yonglin Zhang; Shaoyun Song; Hui Li (Results in Engineering)
Temperature and humidity within grain bulks are two critical factors affecting the safe storage duration of grains. Investigating the heat and moisture transfer mechanisms during storage, along with the coupled interactions among various in-silo factors, enables better prediction of grain storage conditions and supports high-quality grain preservation. In this study, a paddy grain bulk exhibiting humidity stratification inside a grain silo is selected as the research subjet. Based on multi-physics coupling theory, a comprehensive study is conducted on the heat and moisture transfer processes in the paddy grain bulk. A coupled heat and moisture transfer model is established under mechanical ventilation conditions according to the principles of mass, energy, and momentum conservation. Experimental validation is conducted using a custom-built grain silo test chamber, in which temperature and humidity data are collected during ventilation and compared with simulation results to assess model accuracy. The results show that the maximum temperature deviation between simulated and measured values at various monitoring points is 0.94 °C, while the relative humidity error remains within 2 %, demonstrating the model’s high accuracy and adaptability. Building upon existing heat and moisture modeling efforts, this study further deepens the coupling mechanisms and enables dynamic simulation and quantitative analysis of humidity stratification within the grain bulk. These findings provide theoretical support for understanding the mechanisms of humidity stratification and optimizing ventilation-drying strategies.